Advancing green ship design and experiential learning in maritime education - Mauritz H. M. Sibarani; J. Junaidi; Titis Ari Wibowo (Research and Development in Education (RaDEn), 2025)
The maritime sector is increasingly challenged by the need to balance operational efficiency with environmental sustainability. Green ship design and experiential learning have emerged as critical pathways to address these demands. This research investigates how integrating green technologies with practical, hands-on educational approaches can enhance sustainability and workforce readiness in the maritime industry. Building on existing gaps in research, this study explores the perspectives of 13 maritime professionals, 14 lecturers, and 23 graduates, focusing on their experiences with energy-efficient technologies, eco-friendly practices, and the implementation of experiential learning methods. The research adopts a qualitative methodology, employing interviews and focus group discussions, with thematic analysis applied to interpret the data. The findings reveal that green technologies significantly reduce emissions and operational costs while experiential learning, through simulations, internships, and collaborative projects, bridges the gap between theory and practice. Participants reported improved problem-solving skills, adaptability, and readiness to implement sustainable solutions. The synergy between these elements demonstrates their potential to transform the sector by fostering innovation, enhancing workforce competencies, and promoting environmental stewardship. The study concludes that integrating green ship design and experiential learning not only advances maritime sustainability but also sets a precedent for other industries. These findings offer actionable insights for policymakers, educators, and maritime stakeholders to collaboratively build a greener and more sustainable future.